The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1016/j.otohns.2006.11.010
|View full text |Cite
|
Sign up to set email alerts
|

The use of porous polyethylene implants to correct nasal valve collapse

Abstract: Correction of nasal valve collapse with a porous polyethylene implant provided good long-term symptomatic relief of nasal obstruction, but with significant incidence of infection, implant extrusion, and need for revision surgery. The use of this implant should be reserved for cases in which autogenous graft material is not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 17 publications
1
16
0
2
Order By: Relevance
“…Most recently authors have reported the use of implants to strengthen one or both of the nasal valves. Turegun31 used a saddle‐shaped porous polyethylene implant to reconstruct the middle nasal vault, whereas Ramakrishnan46 used the same material as an alar batten. Both report high success rates, although the latter author reported an extrusion rate of 21%.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Most recently authors have reported the use of implants to strengthen one or both of the nasal valves. Turegun31 used a saddle‐shaped porous polyethylene implant to reconstruct the middle nasal vault, whereas Ramakrishnan46 used the same material as an alar batten. Both report high success rates, although the latter author reported an extrusion rate of 21%.…”
Section: Discussionmentioning
confidence: 92%
“…The surgical techniques described addressed collapse of the INV or ENV or both. The studies were grouped on this basis and are presented in Tables I, II, and III 7–48. The lack of any high‐quality studies precludes the pooling of data and thus meta‐analysis is neither possible nor appropriate.…”
Section: Resultsmentioning
confidence: 99%
“…Human data suggest that non‐absorbable alloplastic materials have undesired complications including extrusions or infections following their use in nasal surgeries. Ramakrishnan and colleagues reported an extrusion rate of 21% (4 of 12 patients and 5 of 24 implants) using porous polyethylene as the implant material . Winkler et al reported an extrusion rate of 12% in 662 patients with implantations of high‐density polyethylene and polytetrfluoroethylene for nasal reconstruction .…”
Section: Discussionmentioning
confidence: 99%
“…Ramakrishnan and colleagues reported an extrusion rate of 21% (4 of 12 patients and 5 of 24 implants) using porous polyethylene as the implant material. 17 Winkler et al reported an extrusion rate of 12% in 662 patients with implantations of high-density polyethylene and polytetrfluoroethylene for nasal reconstruction. 18 This study demonstrated that the rod implants made of PLA copolymers elicited expected and contained inflammatory response, with no extrusions observed through 24 months (total of 66 rods placed).…”
Section: Discussionmentioning
confidence: 99%
“…29,30 The use of autogenous tissue avoids the problem of incompatibility, but sometimes fails to provide necessary volume to provide the size and shape. However, septal and conchal cartilages often do not provide adequate volume.…”
Section: Nasal and Premaxillary Augmentationmentioning
confidence: 99%